Information Technology as a Strategic Resource in Encouraging Organizational Change Readiness through the Role of the Human Capital Effectiveness - Hermawan, Iwan; Suharnomo, Suharnomo (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2020)
The application of technology will have a direct strategic impact on the organization. Information technology in the context of infrastructure refers to applications used to create, process, store, and disseminate knowledge to organizations. The capability of information technology will encourage the effectiveness of organizations in creating a competitive advantage. The research direction is to uncover the influence of Information Technology Capability (ITC) on Readiness to Change (RTC) of organizations mediated by the existence of the role of Leadership and Human Capital Effectiveness (HCE). These two big concepts are offered to bridge the research gap. The research sample was 166 design-based fashion manufacture industry in Central Java at the organizational level, consist of 49 males and 117 females respectively. Testing through the Structural Equation Model shows that Information Technology Capability (ITC) has an indirect influence on Readiness to Change (RTC) through Human Capital Effectiveness (HCE) which is greater than through Leadership and HCE.